Link analysis algorithms to handle hanging and spam pages - Patchmuthu, Ravikumar (Curtin University, 2014)
Hanging pages are one of the hidden problems in link structure ranking algorithms and they can be compromised by spammers to induce Link Spam. In this thesis, efficient algorithms have been developed to produce fair and relevant results from Web search engines, by handling hanging pages and detecting Link spam caused by them. The effect of hanging pages in Website Optimisation is also investigated and methodologies were proposed to develop optimised websites.